Socioeconomic Disparity and Depression Among Internal Migrant Workers In Myanmar - MS, Yi; L, Wongsa; S, Kittipong (IIUM Medical Journal Malaysia, 2019)
Background: Over the past few decades, Myanmar has faced mass internal migration to seek job opportunities and pursue a better life. Migration gives rise to unambiguous stress and depression. This study aimed to assess the magnitude of depression and to identify the association between socioeconomic disparity and depression among migrant workers in Myanmar. Methods and Materials: Cross-sectional study was done among 1,201 migrants in Yangon Region. To assess the socioeconomic status, mental health status, accessibility of health care service and Quality of Life by developing self–administered questionnaire. The Generalized Linear Mixed Model was applied to determine the association between socioeconomic disparity and depression after adjusting for other covariates. Result: Their average age was 31.44 ±10.31 years. Gender distribution was not much different. About one third of respondents were factory workers and had low level of education. The magnitude of depression was 38.22% (95%CI= 35.50-41.00). Regarding the socioeconomic disparity, adequacy of income (AOR= 1.79, 95%CI: 1.35-2.37, p value<0.001) and floor surface area of the houses (AOR= 1.21, 95%CI: 1.00-1.47, p value><0.001) were strongly associated with depression. Moreover, other factors that were associated with depression were stress, quality of life and burden of medical service cost. Conclusion: Two-fifth of internal migrant workers suffered depression. The findings highlighted to develop intervention aimed to improve mental health status among migrants. In order to achieve the sustainable development goals, it is important to make investment on mental health of the migrant workers.> <0.001) were strongly associated with depression. Moreover, other factors that were associated with depression were stress, quality of life and burden of medical service cost. Conclusion: Two-fifth of internal migrant workers suffered depression. The findings highlighted to develop intervention aimed to improve mental health status among migrants. In order to achieve the sustainable development goals, it is important to make investment on mental health of the migrant workers.